Presidential Decree-Law No. 23 Of The Year 2015 Amending Certain Provisions of the Building Law and its Promulgating Law No. 119 of the Year 2008 = قرار رئيس جمهورية مصر العربية بالقانون رقم 23 لسنة 2015 بتعديل بعض أحكام قانون البناء والقانون الصادر به رقم 119 لسنة 2008 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic